Strategi Penerapan Outing Class Untuk Meningkatkan Minat Belajar Peserta Didik - Aprilia kusumastuti (Jurnal PGSD, 2025)
Interest is a sense of curiosity, to increase students' sense of interest, perseverance, and skills. Therefore, to foster students' interest in learning, researchers use a learning method using an outing class. Learning outside the classroom or commonly called Outting class is learning outside of school to increase student activity so that they do not get bored easily and also increase student creativity outside the classroom. The purpose of the outing class is to increase student interest in learning through direct experience outside the classroom. The method used in this study is to use a qualitative method with a literature study that focuses on the description and detailed understanding of the phenomenon being studied. The results of this research from the idea of ​​thinking are that the outing class learning strategy can help and foster student interest in learning and with this outting class learning students are able to develop their creativity in learning and make learning less boring. The results of this literature study research can complement theoretically and practically in fostering student interest in learning by using the outting class method.